Incidence trends and long-term outcomes of myocardial infarction in young adults: Does gender matter?. (15th June 2022) - Bruno, Francesco; Moirano, Giovenale; Budano, Carlo; Lalloni, Stefania; Ciccone, Giovannino; Verardi, Roberto; Andreis, Alessandro; Montabone, Andrea; De Filippo, Ovidio; Gallone, Guglielmo; Gilardetti, Marco; D'Ascenzo, Fabrizio; et al.
Abstract: Aims: Data about long-term clinical outcomes of young patients experiencing an acute myocardial infarction (MI) and about the potential impact of gender on juvenile MI incidence and prognosis are scant. Methods and results: Hospital Discharge Register records of Piedmont region (Italy) from 2007 to 2018 were interrogated to identify incident juvenile MI cases and MI recurrences. Patients were considered young if the first MI occurred before or at 47 years of age (5th percentile). Incidence of first juvenile MI event and overall survival were the primary outcomes. Gender differences and survival rate after an MI recurrence were secondary outcomes. Out of 114.816 hospitalizations due to MI, 4482 (3.9%) occurred in people aged ≤47. Average incidence rate of juvenile MI over the study period was 24.5 (23.8-25.2) per 100.000 person-years, with a decline among men and a stable trend among women through the years. The risk of in hospital death was higher for women (1.9% vs. 0.9%, p  = 0.02), while the survival rate at 10 years after the first MI was 94.8%, without gender differences (HR 1.05: 0.69-1.60). MI recurrence occurred in 348 (7.8%) and was less common in women (HR 0.72: 0.52-0.99). After multivariate adjustment, MI recurrence was associated with a significantly higher risk of death at follow-up as compared with a single MI episode (HR 3.05: 1.9-4.80, all CI 95%). Conclusion: Among young patients with MI, women had a higher in-hospital mortality compared to men, but long-term prognosis after hospital discharge did not differ. MI recurrences were associated with increased mortality at follow up. Highlights: There is a paucity of data regarding incidence and prognosis of juvenile MI in Europe. Women had higher in-hospital mortality, but similar long-term prognosis after discharge. MI recurrences were more common in men and associated with mortality at follow-up.